Family conflict mediation centered on the rights of the older person and as a contribution to the foundations of active ageing (PerCursos, 2023)
Conflict mediation is a consensual dialogic practice, oriented to the enhancement of relationships within human communication and intergenerational coexistence, and has shown to be a collaborative tool to prevent and solve family conflicts of ageing individuals, in compliance with the principles and human rights of protection of older persons as bearers of rights. The present article aims at describing the legal, gerontological and ethical foundations of the family mediation practice centered on the rights of the older person, and at showcasing benchmark self-mediation practices arising from research on the topic and their contribution to active ageing. Actively ageing includes having access to every foundation of the life cycle: health, safety, lifelong participation, and learning, as well as the fundamental rights expressed in them. As regards mediation meetings, practical examples show the need for mediators to acknowledge the very heterogeneous and individualized ageing processes of each person, which are embedded in familial, social, communal, and territorial contexts, according to the following principles: human dignity, autonomy, care, familial and intergenerational solidarity.
Keywords: family conflict mediation; principles of protection; human rights of older persons; active ageing